TINGKAT PENGETAHUAN MITRA DAN KELUARGA TENTANG KANKER SERVIK DAN PEMERIKSAAN PAP SMEAR SEBAGAI DETEKSI DINI (SKRINING) KARSINOMA SERVIK - Analysa Analysa; Ni Putu Primadi (UNHI Press, 2023)
Cervical cancer is one of the most common types of cancer suffered by women in developing countries, including Indonesia. This condition occurs due to lack of knowledge about prevention and detecting early symptoms of cervical cancer, especially in areas far from public health service centers. The purpose of this community partnership program is to help government programs to reduce the incidence of cervical cancer through counseling and interactive dialogue to increase the knowledge of partners and their families about cervical cancer and pap smears as screening for cervical cancer, which was carried out in the village of Gali Ukir Pupuan Tabanan, then carried out assisting partner family members in providing information about cervical cancer and pap smears to the surrounding community, as well as visits to monitor family members who are willing to carry out pap smears, and providing assistance in the form of pap smear examinations, giving antiseptics for the vagina, pocket books that can be used as guidelines for giving information about cervical cancer and its prevention, as well as providing a blender that can be used to make anti-septic from nearby plants and to make nutritious drinks to increase immunity. The results obtained are in the form of increased knowledge and changes in thinking patterns about cervical cancer and there are family members who do pap smear examinations.